Alright, buckle up, buttercup. To factor the expression 7x + 21 - 14y, you first want to look for common factors within the terms. In this case, you can factor out a 7 from all the terms, leaving you with 7(x + 3 - 2y). And there you have it, all factored and ready to roll.
Without an equality sign the given terms of an expression can't be classed as an equation and so therefore an answer is not possible.
If: 3x-3 = 7x+21 Then: x = -6
x2 + 7x + 6 = (x + 6) (x + 1)
If you mean: x squared -7x +12 then it is (x-3)(x-4) when factored
(10x + 3)(x - 1)
7(x - 2y)
It is: 7(x+2y)
The GCF is 7.
set it up as x+5y=10 and 7x-14y=49 on top of each other and then multiply x+5y=10 by -7. That gives you -7x-35y=-70. cross out the X's and add the Y's. -21y=21 divide and get -1=y then sub. for x and solve. X=15 and X=5
Without an equality sign the given terms of an expression can't be classed as an equation and so therefore an answer is not possible.
Since 7x is a factor of 14xy, it is automatically the GCF.
(y-12)(y-2)
(3y - 2)(y - 4)
(7x + 8)(7x - 8)
12x - 4 = 7x - 21 12x -7x = -21 + 4 5x = -17 x = -3.4
(7x + 8)(7x - 9)
If: 3x-3 = 7x+21 Then: x = -6